Searching for the Nanoscopic-Macroscopic Boundary - Altbir-Drullinsky, D (2013)
Several studies have focused on the size-dependent properties of elements, looking for a unique definition of the nanoscopic-macroscopic boundary. By using a novel approach consisting of an energy variational method combined with a quantum Heisenberg model, here we address the size at which the ordering temperature of a magnetic nanoparticle reaches its bulk value. We consider samples with sizes in the range 1-500 nm, as well as several geometries and crystalline lattices and observe that, contrarily to what is commonly argued, the nanoscopic-microscopic boundary depends on both factors: shape and crystalline structure. This suggests that the surface-to-volume ratio is not the unique parameter that defines the behavior of a nanometric sample whenever its size increases reaching the bulk dimension. Comparisons reveal very good agreement with experimental evidence with differences less than 2%. Our results have broad implications for practical issues in measurements on systems at the nanometric scale. © 2013 Elsevier B.V.
Keywords: Nanostructure; Ordering temperature; Nanoscopic-macroscopic boundary; Quantum Heisenberg variational approach